2008
DOI: 10.1590/s0103-64402008000400010
|View full text |Cite
|
Sign up to set email alerts
|

Bond strength of a pit-and-fissure sealant associated to etch-and-rinse and self-etching adhesive systems to saliva-contaminated enamel: individual vs. simultaneous light curing

Abstract: This study evaluated in vitro the shear bond strength (SBS) of a resin-based pit-and-fissure sealant [Fluroshield (F), Dentsply/Caulk] associated with either an etch-and-rinse [Adper Single Bond 2 (SB), 3M/ESPE] or a self-etching adhesive system [Clearfil S3 Bond (S3), Kuraray Co., Ltd.] to saliva-contaminated enamel, comparing two curing protocols: individual light curing of the adhesive system and the sealant or simultaneous curing of both materials. Mesial and distal enamel surfaces from 45 sound third mola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
1
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 13 publications
(19 reference statements)
3
32
1
6
Order By: Relevance
“…Occurrence of marginal microleakage following the application of CR-based fissure sealant was similar to that obtained with SAR-based fissure sealant -with or without prior PA etching. This similarity was due to the presence of functional monomers in the SARbased fissure sealant used in this investigation, which improved its flowability and penetrability into the capillary-like spaces of etched enamel surface, thereby resulting in improved adhesion and good sealing 40,41) . Ganesh and Shobha 42) reported that the sealing ability of CR-based fissure sealants is better than that of GI-based fissure sealants, as indicated by a lower occurrence of marginal microleakage.…”
Section: Discussionmentioning
confidence: 88%
“…Occurrence of marginal microleakage following the application of CR-based fissure sealant was similar to that obtained with SAR-based fissure sealant -with or without prior PA etching. This similarity was due to the presence of functional monomers in the SARbased fissure sealant used in this investigation, which improved its flowability and penetrability into the capillary-like spaces of etched enamel surface, thereby resulting in improved adhesion and good sealing 40,41) . Ganesh and Shobha 42) reported that the sealing ability of CR-based fissure sealants is better than that of GI-based fissure sealants, as indicated by a lower occurrence of marginal microleakage.…”
Section: Discussionmentioning
confidence: 88%
“…Studies have shown that the SBS between sealant and enamel surface decreases significantly under conditions of salivary contamination (4). Because of the high enamel reactivity induced by phosphoric acid etching, even minute exposures to saliva, as brief as 1 s, could be sufficient to create a pellicle that partially occludes the enamel pores, causing ultrastructural alterations and preventing formation of the resin tags responsible for mechanical retention (8).…”
Section: Discussionmentioning
confidence: 99%
“…Fluroshield™ showed higher SBS means when it was associated with adhesive systems without contamination. This is likely due to the great capacity of single-bottle adhesives to flow deeply into capillary-like spaces of the etched enamel surface and produce an optimal resin tag penetration and enhanced adhesion (4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Feigal [18] reported that adding a bonding agent layer between sealant and saliva contaminated enamel allowed adequate bond strength and retention of resin sealants. However, in a contrasting study, Gomes-Silva [19] concluded that individual or simultaneous curing of the intermediate bonding agent layer and the resin sealant did not seem to affect bond strength to saliva-contaminated enamel. …”
Section: Resultsmentioning
confidence: 96%